Gut Microbiota of Ostrinia nubilalis Larvae Degrade Maize Cellulose - Li, Junfeng; Wang, Siran; Zhao, Jie; Dong, Zhihao; Shao, Tao (Frontiers in Microbiology, 2022)
Most arthropod guts harbour diverse microbiota for symbiotic digestion. The European corn borer (ECB), Ostrinia nubilalis (Hübner), is a devastating pest that feeds the lignocellulose-rich tissues of maize plants. However, the potential role of ECB gut microbes in degrading maize cellulose remains unexplored. Here, we investigated the gut microbiota of ECB fed with different diets and their potential function in maize lignocellulose degradation. The diversity and composition of gut bacterial communities varied dramatically between the ECB larva fed with artificial diets (ECB-D) and maize plants (ECB-M). Draft genomes of the microbial consortia from ECB-D and ECB-M showed that the principal degraders of cellulose mainly belonged to Firmicutes or Proteobacteria and they were primarily found in the midgut. The cellulolytic microbial consortia contained genes encoding various carbohydrate-active enzymes (CAZyme). Furthermore, scanning electron microscopy revealed significant breakdown of lignocellulose in maize treated by the two microbial consortia for nine days in vitro. Metabolomic analyses show that maize particles treated by two microbial consortia generate distinctive metabolomic profiles, with enrichment for different monosaccharides (i.e., Glucose, Rhamnofuranose, Isomaltose, and Cellobiose) and amino acids (i.e., Threonine, Histidine, and Lysine). The results indicated that the diet of the host impacted the composition and function of its gut microbiota and ECB exploited specific gut microbes to digest maize lignocellulose with distinctive products. Our study provides valuable microbiota resources for lignocellulose bioconversion.